2008
DOI: 10.1007/s11090-008-9144-0
|View full text |Cite
|
Sign up to set email alerts
|

Naphthalene and Acenaphthene Decomposition by Electron Beam Generated Plasma Application

Abstract: The application of non-thermal plasma generated by electron beam (EB) was investigated in laboratory scale to study decomposition of polycyclic aromatic hydrocarbons like naphthalene and acenaphthene in flue gas. PAH compounds were treated by EB with the dose up to 8 kGy in dry and humid base gas mixtures. Experimentally established G-values gained 1.66 and 3.72 mol/100 eV for NL and AC at the dose of 1 kGy. NL and AC removal was observed in dry base gas mixtures showing that the reaction with OH radical is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The concentration of OH-radical behaves as non-monotonous function of the dose lowering down to 1.6 ppb on the interval D = 1-4 kGy and then increasing up to 4 ppb at D = 20 kGy. The model predictions of NL decomposition, the simplest representative of the PAHs compounds, and their comparison with experimental data [8] are given in Fig. 5 for two gas mixtures: N 2 /O 2 /H 2 O (84/10/6, vol.%) and N 2 /O 2 (90/10, vol.%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The concentration of OH-radical behaves as non-monotonous function of the dose lowering down to 1.6 ppb on the interval D = 1-4 kGy and then increasing up to 4 ppb at D = 20 kGy. The model predictions of NL decomposition, the simplest representative of the PAHs compounds, and their comparison with experimental data [8] are given in Fig. 5 for two gas mixtures: N 2 /O 2 /H 2 O (84/10/6, vol.%) and N 2 /O 2 (90/10, vol.%).…”
Section: Resultsmentioning
confidence: 99%
“…The leading role of OH radicals in the degradation of aromatic molecules is due to both Fig. 6 Products of NL decomposition under EB irradiation in wet gas mixture: 1-naphthalene, 2-nitronaphthalene, 3-products of nitronaphthalene decomposition, 4-2-formyl-cinnaldehyde, 5-naphthol; lines are the model predictions, points are the experimental data [8] Plasma Chem Plasma Process their higher concentration in the irradiated gas and quite a high value of their reaction rate constant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results demonstrated the insignificant role of adsorption for PAHs removal (Callén et al, 2007). Naphthalene (NL) and acenaphthene (AC) decomposition in gas mixture was studied in lab scale experiment (Ostapczuk, et al, 2008b). It was found that NL was more easily decomposed than AC, G-values for these two compounds were 1.66 and 3.72 mol/100 eV for NL and AC at the dose of 1 kGy , respectively.…”
Section: Naphthalene(c10h8)mentioning
confidence: 93%
“…Non-thermal plasmas (NTPs) are regarded as promising advanced oxidation processes (AOPs) for the sustainable and efficient removal of organic pollutants from wastewater (Ognier et al 2009;Hijosa-Valsero et al 2013;Iya-Sou et al 2013;Jamróz et al 2014;Magureanu et al 2015;Stratton et al 2015) and polluted gas (Ostapczuk et al 2008;Malik et al 2011;Jolibois et al 2012;Bao et al 2014;Zhang et al 2015). During the last few years, they have started to be examined for soil remediation (Wang et al 2010;Lou et al 2012;Ognier et al 2014;Aggelopoulos et al 2015a).…”
Section: Introductionmentioning
confidence: 99%